POLITISI PEREMPUAN DAN KORUPSI : MENCARI SOLUSI ATAS DILEMA POLITIK KESETARAAN GENDER DI ERA REFORMASI - Juwita Hayyuning Prastiwi; Wimmy Haliim (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Theoretically and empirically, the presence of women in politics is believed to reduce corruption behaviour. Unfortunately, in Indonesia, such essential categorization is not proven to reduce corrupt behavior considering that women can also be an executor, connoisseur, and even intermediaries of corrupt behavior. Women, as one category of sex, is not sufficient to analyze the role of women in corruption act, because woman is bounded by culture, religion, ethnicity and social class. Based on this background, this study attempts to find the root of the problem and the solution for woman politician in corruption act. By using electoral system theory and political party as theoretical analysis and literature study as the method, this study identifies that behavior of women corruptor cannot be separated from the power of elites in political parties and parliaments. The strong power of the oligarchic elite in political parties and parliaments itself is the result of an open proportional election system which has an impact on the high competitiveness of parties, so that led to high cost of political to be beared by women. Ultimately, to improve such conditions, the engineering of electoral and party systems is most likely to be a solution, as both are easy to intervene by state actors and civil society groups. In conclusion, this paper shows that political parties have to be responsible in promoting gender equality, and willing to review the quota and zipper system in relation to the proportional systems